"Stepping with ease towards a new way of living" – experiences of physical activity 5 years after bariatric surgery. (3rd July 2017) - Stenmark Tullberg, Helene; Fagevik Olsén, Monika; Shams, Kima; Wiklund, Malin
Abstract: Aim: Obesity has many negative health consequences. The only evidence-based treatment with long-term effects on weight reduction is bariatric surgery. There is limited knowledge on how patients experience physical activity several years after such surgery. The aim of the study was, therefore, to describe how patients who have undergone bariatric surgery experience physical activity more than 5 years after the operation. Methods: In this qualitative interview study, 12 patients (10 women/2 men) were included. They had all undergone laparoscopic bariatric surgery >5 years previously because of super obesity (BMI >50 kg/m 2 ). The patients were interviewed about their experiences of physical activity and the interviews were recorded and transcribed verbatim. The analysis was made with qualitative content analysis using an inductive approach as described by Graneheim and Lundman. The local research ethics committee approved the study. Results: Five themes appeared focusing on different aspects of activity in life: daily life, family, occupation, physical exercise and emotions. Opportunities and obstacles emerged as categories. Conclusion: The study indicates that several years after the obesity surgery most of the patients still experience many obstacles that interfere with the experience of physical activity as a natural part of daily life. These data suggest that assessment of barriers to physical activity remain an important step in physical activity counselling several years after bariatric surgery.